Strikes of physicians and other health care workers in sub-Saharan African countries: a systematic review - Manguele, Alexandre Lourenço Jaime; Sidat, Mohsin; Ferrinho, Paulo; Cabral, António Jorge Rodrigues; Craveiro, Isabel (Frontiers in Public Health, 2024)
Introduction Strikes in the health sector have been of growing concern, given their disruptive nature, negatively impacting the provision of health care and jeopardizing the well-being of patients. This study aims to identify the main actors, the reasons behind industrial actions protests, strikes and lockouts (IAPSL) in sub-Saharan African countries and their impact on health care workers (specifically doctors) and health services, as well as to identify the main strategies adopted to reduce their impact on healthcare services. Methods Studies published between January 2000 and December 2021 and archived in MEDLINE, Google Scholar, Scopus, ProQuest, and Science Direct were included. Quantitative, observational (i.e., cohort, case-control, cross-sectional, and ecological) and experimental studies, as well as mixed methods, quasi-experimental, and qualitative studies were eligible Results A total of 5521 studies were identified and after eliminating duplicates, applying the inclusion criteria, and assessing the risk of bias, a total of 11 studies were included in the review. Nurses and doctors are the actors most commonly involved in strikes. The main causes of strikes were salary claims and poor working conditions. The main strategies adopted to mitigate the strike consequences were to restrict services and prioritize emergency and chronic care, greater cooperation with the private sector and rearrange tasks of the available staff. The strikes led to a reduction in hospitalizations and in the number of women giving birth in health units, an increase in maternal and child morbidities and delays in the immunization process. Increased mortality was only reported in faith-based hospitals. Discussion This evidence can assist decision-makers in developing strategies and interventions to address IAPSL by health care workers, contributing to strengthen the health system. Strikes in the health sector disrupt healthcare services provision and compromise the well-being of patients, especially the most disadvantaged, with consequences that may be difficult to overcome ever. The potential health impacts of strikes highlights the importance of their prevention or timely resolution through regulation and negotiations to balance the rights of health care workers and the rights of patients. Systematic review registration https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=334173, identifier CRD42022334173.